Effect of season of production on storage and production behaviour of potato (Solanum tuberosum) mini-tubers - SHARMA, ASHWANI K; PANDEY, K K (The Indian Journal of Agricultural Sciences, 2016)
Storage, sprouting and production behaviour of different grades of potato mini-tubers of cv. Kufri Girdhari produced during summer (Kharif) and autumn seasons in high hills of north-western Himalaya (9 000 feet amsl) was studied. The study revealed that mini-tubers produced during both the seasons in the high hills store well under ambient conditions till the next potato planting season, i.e. April. Number of sprouts and length of longest sprout per minituber as well as average weight per tuber at the end of storage period was affected significantly by the season of production as well as grade of mini-tubers. However, total physiological loss in weight of mini-tubers from two seasons was almost same but was affected significantly by the grade of mini-tuber. Mini-tubers from both the seasons resulted in same yield and number of tubers per hectare. A gradual and consistent increase in the number of tubers as well as in potato yield with the increasing size of mini-tuber was noticed. Similar field productivity of mini-tubers from two seasons is in total support of the practice of taking two crops of mini-tubers (from in vitro plantlets) under protected conditions. The information generated will be helpful in boosting the fast multiplication of elite planting material of potato in the high hills of north western Himalaya.